DESIMINASI MODEL PENGEMBANGAN TERNAK RUMINANSIA BERBASIS TANAMAN PANGAN DI KABUPATEN KUPANG - Siviardus Marjaya; Alfred U. K. Ngaji (Politeknik Pertanian Negeri Kupang, 2019)
The dissemination of a food crop-based ruminants development model will determine the success of a commodity that can compete in the market, as well as open up employment opportunities and provide income for farmers. This research aims to; (1) disseminating a model of food crop-based ruminants development in farmer groups in Kupang Barat sub-district, Kupang Regency, (2) producing an effective and efficient food-based ruminant animal development model in supporting food self-sufficiency so that it can maintain food security for the community at Kupang Regency, (3) increases the sustainability and ecological balance for the long-term growth and production of plants and livestock. Production data obtained during one planting season of corn, cabbage flowers, beans and a period of raising cattle in 2019. The data analysis model used in this study is the analysis of costs, revenues and profits of farming according to Tohir (1980). The results of the analysis show that the dissemination of a food crop-based ruminant development model is very beneficial for farmers with a magnitude of the profit ratio between revenue and cost of 8.6. This means that at the expense of a fee of one rupiah, an income of 8.6 rupiah would be obtained.